The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.1042/bj2030015
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) transport in human blood serum. Studies of nickel(II) binding to human albumin and to native-sequence peptide, and ternary-complex formation with l-histidine

Abstract: Detailed studies are reported on the Ni(II)-binding site of human serum albumin (HSA) and the results are compared with those obtained from the N-terminal native-sequence peptide, l-aspartyl-l-alanyl-l-histidine N-methylamide (Asp-Ala-His-NHMe). Equilibrium dialysis of HSA and Ni(II) in 0.1m-N-ethylmorpholine/HCl buffer, pH 7.53, demonstrates a specific Ni(II)-binding site on the protein. l-Histidine, the low-molecular-weight Ni(II)-binding constituent of human serum, is shown to have a greater affinity for Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 22 publications
3
48
0
1
Order By: Relevance
“…Other interesting features that were observed are a small peak at 410 nm and a shoulder at 310 nm. A peak at 420 nm has been observed in nickel-containing human serum albumin, and the intensity of this peak increased with increasing pH and was attributed to Ni 2ϩ coordinated in a square planar or square pyramidal geometry (36). The nickel content of this CooJ sample is less than 0.1 Ni 2ϩ atom/CooJ monomer, and the feature at 410 nm did not change with increasing pH, ruling out a nickel species similar to that found in human serum albumin.…”
Section: Identification Of the Cooj Protein-mentioning
confidence: 99%
“…Other interesting features that were observed are a small peak at 410 nm and a shoulder at 310 nm. A peak at 420 nm has been observed in nickel-containing human serum albumin, and the intensity of this peak increased with increasing pH and was attributed to Ni 2ϩ coordinated in a square planar or square pyramidal geometry (36). The nickel content of this CooJ sample is less than 0.1 Ni 2ϩ atom/CooJ monomer, and the feature at 410 nm did not change with increasing pH, ruling out a nickel species similar to that found in human serum albumin.…”
Section: Identification Of the Cooj Protein-mentioning
confidence: 99%
“…Upon treatment with hydrochloric acid, absorption intensities below 265 nm were increased, but the max and the ⑀ 277.5 values remained unchanged, suggesting that chromophores are not acid-labile. CooC contains six cysteine residues, and thus we examined the visible region of the spectrum in detail to see whether CooC has an absorbance at 420 nm that might suggest the presence of an Fe 4 S 4 cluster (31, 37) or of nickel d 3 d transition of nickel-binding protein (38), but A 420 was not observed. Analyses of iron content and of the UV spectrum confirmed that CooC is not an iron-sulfur protein.…”
Section: Effect Of Cooctj Mutations On Codh Activity-mentioning
confidence: 99%
“…This bears a striking resemblance to the Cu 2ϩ binding motif (NH 2 -XXH) at the N terminus of human serum albumin (HSA) (40,41). This site is responsible for Cu 2ϩ transport in blood plasma (42) and has a tight 1.0 pM affinity for Cu 2ϩ , whereas N-terminal tripeptide models possess a subpicomolar affinity (43)(44)(45)(46).…”
mentioning
confidence: 99%